A Current Fed Two-Inductor Boost ConverterWith an Integrated Magnetic Structure and Passive Lossless Snubbers for Photovoltaic Module Integrated Converter Applications - Li, Q.; Wolfs, Peter (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2007)
In this paper, a photovoltaic (PV) module integrated converter is implemented with a current fed two-inductor boost converter cascaded with a line frequency unfolder. The current source is a sinusoidally modulated two-phase buck converter with an interphase transformer. The boost cell operates at a fixed duty ratio and has an integrated magnetic structure. The two inductors and the transformer are integrated into one magnetic core. Passive lossless snubbers are employed to recover the energy trapped in the transformer leakage inductance and to minimize the switching losses. The two-inductor boost converter output interfaces with the mains via an unfolding stage, where the MOSFETs are driven by the PV gate drivers. Experimental results are provided for a 100-W converter developing a single phase 240-V 50-Hz output.